Merebaknya Intoleransi (Hate Speech dan Hate Crime) dalam Politik Indonesia - Munandzirul Amin (Madani Jurnal Politik dan Sosial Kemasyarakatan, 2020)
Democracy provides a place for us to learn to live with the enemy because only democracy allows tension and paradox, which comes from freedom, to occur in society. In contrast to the New Order era, we can now enjoy freedom of opinion and association. This freedom can in turn produce tension. The relationship between elements of society with one another, or the relationship between the state and elements of society, can be tense because of differences in interests in regulating social and political order. Meanwhile, Indonesian society witnessed the paradox which also originated from freedom. This, for example, is shown by the emergence of intolerant groups such as the Islamic Defenders Front (FPI) and Hizb ut-Tahrir Indonesia (HTI). Even organizations such as HTI are of the view that democracy is not in accordance with the teachings of Islam in terms of sovereignty in the hands of the people, what should determine that is the preogrative right of Allah SWT. The government in the view of HTI only implements sharia and determines administrative technical issues.